2019
DOI: 10.1002/pssr.201900186
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet‐ and FlexTrail‐Printing with Low Silver Consumption for Silicon Heterojunction Solar Cells

Abstract: Bifacial busbarless silicon heterojunction (SHJ) solar cells with an edge length of 156.8 mm are metalized using a commercially available Ag nanoparticle ink on the front side. By means of inkjet‐printing, a maximum conversion efficiency of 23.3% is achieved. The influence of the inkjet‐printed layer number per contact finger, which is varied from one to five, on cell performance is investigated in detail. Optima are found for one and two layers, which ensure both high efficiency and low silver consumption. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…[25] This has been considered in previous FlexTrail-related publications by correction analysis. [22,24] It is the goal of current work to demonstrate an increase of FlexTrail-printed fingers' height by keeping finger width as low as possible and to evaluate such metallization on the front side of SHJ solar cells. For this purpose, the silver loading of the printing medium has been increased from 50% wt to 87% wt in collaboration with an external partner.…”
Section: Flextrail Printingmentioning
confidence: 99%
See 2 more Smart Citations
“…[25] This has been considered in previous FlexTrail-related publications by correction analysis. [22,24] It is the goal of current work to demonstrate an increase of FlexTrail-printed fingers' height by keeping finger width as low as possible and to evaluate such metallization on the front side of SHJ solar cells. For this purpose, the silver loading of the printing medium has been increased from 50% wt to 87% wt in collaboration with an external partner.…”
Section: Flextrail Printingmentioning
confidence: 99%
“…In previous publications, SHJ solar cells’ front metal contacts with feature sizes of (16.0 ± 1.0) μm have been presented using an ink with 50% wt silver loading. [ 22,24 ] However, the height of FlexTrail‐printed contact fingers was determined to be in the range of 0.2 μm only. This results in resistive losses of the solar cell and, additionally, can lead to fill factor (FF) overestimations in solar cell IV‐measurements.…”
Section: Flextrail Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…One such application is Ag‐coated Cu paste, [ 18 ] particularly for HJT cells. [ 10 ] By using a coated Ag on Cu particles, the Ag usage can be reduced by 30–50%. A more exciting alternative would be to use a Cu paste that is free of Ag.…”
Section: Introductionmentioning
confidence: 99%
“…A rotary screen printing method developed by Lorenz et al [9] has short printing cycles and a low Ag consumption of about 6-9 mg W À1 . Schube et al [10] reported a novel metallization technology called FlexTrail-printing, and very low Ag consumption 0.05 mg W À1 has been achieved by using Ag nanoparticle ink. The use of dispensing equipment has also been developed for the metallization of solar cells, [11] with 0.54 mg per Ag finger being reported.…”
Section: Introductionmentioning
confidence: 99%